Germline activating sequence variations in RASopathy spectrum genes: genotype–phenotype correlation in a North Indian cohort - Gupta, Shifali; Srivastava, Priyanka; Daniel, Roshan; Bhardwaj, Chitra; Kaur, Parminder; Bawa, Pratibha; Kumari, Anu; Bhadoriya, Ravi Pratap Singh; Peters, Mrinali; Kaur, Anupriya; Panigrahi, Inusha (Frontiers in Genetics, 2025)
BackgroundRASopathies represent a group of genetically heterogeneous developmental disorders caused by germline variants in genes regulating the RAS/MAPK signalling pathway. These syndromes share overlapping clinical features, complicating diagnosis. Dysregulation of this pathway disrupts normal development and contributes to diverse phenotypic manifestations. In this study, we conducted a comprehensive clinico-genetic correlation analysis in a North Indian cohort to identify causative genetic variants. As an exploratory approach, we also applied bioinformatic tools to identify potential drug–gene interactions.MethodsWe enrolled 84 patients with clinical suspicion of RASopathy spectrum disorders. Whole exome sequencing (WES) was performed to detect pathogenic variants. Clinical data were systematically collected and analysed for genotype–phenotype correlation. Potential therapeutic agents were queried using the Drug–Gene Interaction database (DGIdb).ResultsPathogenic or likely pathogenic variants in RASopathy-related genes were identified in 46 cases, including 14 with neurofibromatosis. Two patients had variants of unknown significance (VUS) in MAPK1 and LZTR1. PTPN11 variants were detected in 12 patients, while variants in LZTR1, MAP2K2, BRAF, NRAS, HRAS, RAF1, RIT1, SOS1, and SOS2 were found in 20 others. All identified variants were heterozygous missense mutations, consistent with autosomal dominant inheritance. The most common clinical features were short stature (64.7%), downslanting palpebral fissures (38.23%), and chest wall deformities (35.29%). A trend was observed for the association between PTPN11 and SOS1 variants and pulmonary stenosis, though not statistically significant due to the small cohort size. Unique phenotypic findings associated with different variants in RASopathy spectrum genes were noted. Exploratory DGIdb analysis highlighted candidate drug–gene interactions that may inform future research directions.ConclusionOur findings underscore the clinical and genetic diversity of RASopathies in the Indian population and highlight the role of next-generation sequencing in early and accurate diagnosis. While exploratory drug–gene interaction analysis provides hypothesis-generating insights, clinical translation requires rigorous validation in functional studies and clinical trials.